An analytical model of geosynthetic-reinforcement pile-supported embankments simultaneously considering pile–soil differential settlement and geosynthetic-soil interface friction - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Lei Zhang; Hanyan Gu; Yanjun Qiu (European Journal of Environmental and Civil Engineering, 2026)

Coordinating carbon trading and green certificates for low-carbon cross-regional electricity transmission: Evidence from Inner Mongolia, China - Xin Zhang; Boyi Li; Richao Cong; Toru Matsumoto; Rong-Gang Cong (Energy and Climate Change, 2026)

Potassium channels in cancer: from hallmarks to therapeutic targeting - Yi-ling Zhang; Rong-jia Shi; Xin-hua Liang (Journal of Physiology and Biochemistry, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Multi-omics integration elucidates molecular mechanisms underlying distinctive meat quality in Liping cattle versus Angus hybrid and Simmental breeds - Longxin Xu; Xin Wang; Yuanfeng Zhao; Chunxia Zheng; Jing Liu; Kaikai Zhang; Wenzhang Zhou; Rong Yang; Di Zhou; Zhongling Jian; Yongcai Zhu; Junda Wu; et al. (Food Research International, 2026)

Regulating proton back-diffusion to enhance lithium sulfate conversion in bipolar membrane electrodialysis - Rong Zhang; Lingyun Wang; Xin Wang; Zhe Yu; Wenkai Wang; Ming Tan; Yang Liu; Yang Zhang (Desalination, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Integrated network toxicology, transcriptomics, and metabolomics revealed the potential mechanisms of aluminum-induced testicular injury - Siyu Liao; Liqing Huang; Yusi Zhou; Xin Zhang; Shaofeng Huang; Linjun Yu; Shiman Zhu; Wei Chen; Rong Wang; Haimei Qin (Food and Chemical Toxicology, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

The microalgae-bacteria symbiotic inoculation enhances sandy soil multifunctionality and wind erosion resistance through microbial network reorganization - Lianhao Sun; Xin Sun; Haonan Zhang; Hui Nie; Chong Li; Xin Liu; Haidong Li; Xiongfei Zhang; Qianqian Liu; Jingyi Zeng; Weiqi Meng; Guoshuai Hou; et al. (CATENA, 2026)

A robot herding strategy combining CMFF and MPC for shepherding - Hongbo Liu; Ping Song; Gang Liu; Xiaoping Xin; Yuping Rong; Luyu Ding; Junyao Gao; Zhuoming Wang; Yinglong Zhang; Pengzhen Li (Computers and Electronics in Agriculture, 2026)

Mechanistic insights and mitigation strategies for brominated dioxin formation from thermal treatment of hexabromocyclododecane waste - Heng Zhang; Lyumeng Ye; Junkai Lin; Zhiyuan Xu; Rong Jin; Dongyao Chen; Xin Zhou; Bingcheng Lin; Minghui Zheng (Waste Management, 2026)

Characterization of CYP402C5 associated with field resistance to three neonicotinoids in Bemisia tabaci - Chao Wang; Rong Zhang; Jing Yang; Mingjiao Huang; Hantang Lu; Ying Zhang; Youjun Zhang; Junkai Li; Xin Yang (Pesticide Biochemistry and Physiology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

NPFF2 regulate thiamethoxam resistance by over-expressing CYP6CX4 in Bemisia tabaci - Ying Zhang; Rong Zhang; Hantang Lu; Buli Fu; Xiaojie Wu; Hu Xue; Xuegao Wei; Youjun Zhang; Xin Yang (Pesticide Biochemistry and Physiology, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

pH-responsive, self-lubricating hyaluronic acid-chondroitin sulfate-chitosan hydrogel for articular cartilage repair - Haofeng Qiu; Jingfang Zheng; Zheyu Yao; Ximing Cai; Gaoke Pan; Xufeng Mao; Xin Zhao; Lei Shao; Dangsheng Xiong; Rong Wang; Yi Zhang (Carbohydrate Polymers, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Exploring root-mediated Erwinia amylovora invasion mechanism in Korla fragrant pear (Pyrus sinkiangensis) - Lili Han; Yue Sun; Xin Deng; Jiehua Wang; Feng Zhang; Weimin Chen; Rong Lei (European Journal of Plant Pathology, 2026)

PM2.5 exposure exacerbates cerebral infarction via HPG axis downregulation and pituitary lipid metabolism dysregulation in mice - Xin lv; Guanhui Pei; Lijuan Liu; Zhou zhou; Yicong Zhou; Binbin Wang; Chaoyue Meng; Ruomeng Chen; Qiang Yao; Ge Bai; Xuelin Wang; Minghan Zhao; et al. (NeuroToxicology, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Bioaerosol multi-pollutant source localization in urban microclimates using an improved particle swarm optimization method with restricted search capabilities - Zhijian Liu; Yixiang Ma; Chenxing Hu; Haiyang Liu; Hongliang Zhang; Xin Li; Zhenhai Sun; Rui Rong; Zhijian Dong; Xiang Zhao; Guangpeng Yao (Sustainable Cities and Society, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Biochar aging-driven cadmium release in paddy soils: Mechanistic insights into adsorption capacity loss and biochar feedstock-specific risks - Ze-ning Yu; Xiao-qing Zhang; Fei-mei Chen; Rong-liang Qiu; Kuan Zhou; Xin-xian Long (Journal of Environmental Sciences, 2026)

Numerical analysis of heat transfer and flow characteristics of ice slurry in flat-sided oval pipe - Yuwei Fan; Xin-Rong Zhang (International Journal of Refrigeration, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Engineering catalytic sites in ZnIn2S4 via Mg doping: A S-to-In shift toward enhanced photocatalytic H2 evolution - Yan Wang; Yuqi Shi; Xin Chong; Chao Wang; Rong Fu; Chang Liu; Yuelan Zhang (Chemical Engineering Journal, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Guaianolide sesquiterpenoids from Chrysanthemum indicum L. alleviate rheumatoid arthritis by targeting of NLRP3 inflammasome pathway - Gui-Min Xue; Hao Feng; Dong-Rong Zhu; Xin-Xin Guo; Ding-Qiao Xu; Yan-Jun Sun; Yan-Le Zhi; Zhi-Qiang Zhang; Guo-Sheng Li; Fa-Wu Dong; Jin-Feng Xue (Phytochemistry, 2026)

Photoelectron-driven modulation of carbon metabolism enhances hydrogen production in a ZnIn2S4-Shewanella oneidensis biohybrid system - Xue-Meng Wang; Hao-Yu Li; Kai-Li Wang; Zhi-Xuan Zhang; Yu-Xin Cao; Ya-Lian Ma; Rong Chen (Bioresource Technology, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Bidirectional electron transfer enabled by dual electric fields for efficient 4-nitrophenol removal on a bifunctional FeCoNiP/PCN heterojunction - Yan Wang; Chang Liu; Rong Fu; Chao Wang; Xin Chong; Yuqi Shi; Yuelan Zhang (Journal of Environmental Chemical Engineering, 2026)

Research progress on the structure of edible fungi polysaccharides and their anti-obesity mechanisms via the regulation of intestinal microbiota and metabolites - Xin Wei; Weiya Rong; Liyang Jin; Limin Zhang; Daoqin Ren; Yue Jiang; Jinling Cao; Shaojun Yun; Feier Cheng; Wenfei Zhao; Yong Li; Mingchang Chang; et al. (Food Bioscience, 2026)

Antibacterial mechanism of Sanguinarine against Klebsiella pneumoniae and its efficacy in reducing bacterial contamination in milk - Ruiying Wang; Diangang Han; Tianlong Hu; Rong Zhao; Yanlin Li; Qiqi Pu; Ju Zeng; Xiong Dai; Long Zhang; Jige Xin (Food Bioscience, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Case study of aircraft icing in-cloud measurements and explicit supercooled water prediction in Eastern China - Liping Luo; Ming Xue; Xin Xu; Lin Deng; Junxia Li; Rong Zhang (Atmospheric Research, 2026)

Genome-wide CRISPR/Cas9 knockout screen identifies host factors essential for bovine parainfluenza virus type 3 replication - Jinyang Hao; Xiaoran Gao; Christine Light; Yuze Sun; Sha Lu; Yu Tian; Xia Gao; Yuan Su; Jie Gao; Xin Huang; Qianyi Zhang; Jinliang Wang; et al. (Science China Life Sciences, 2026)

Efficacy and Safety of Temozolomide for the Treatment of Advanced or Recurrent Ependymoma: A Meta-Analysis - Rong Zhang; Binyan Liu; Zhuang Kang; Shenglan Li; Yingfan Sun; Jiachen Wang; Xin Yang; Shuo Yin; Feng Chen; Wenbin Li (Journal of Pharmaceutical Innovation, 2026)

Tidal Modulation of Waves over the Changjiang River Estuary: Long-Term Observations and Coupled Modeling - Zhikun Zhang; Zengrui Rong; Xin Meng; Pixue Li; Tao Qin (Journal of Marine Science and Engineering, 2026)
Tidal-scale wave modulation is a critical yet complex process in macro-tidal estuaries. This study investigates semidiurnal wave modulations in the Changjiang River Estuary (CRE) using unique, long-term in situ observations and high-resolution ADCIRC–SWAN coupled simulations. Pronounced semidiurnal signals are identified in significant wave height (Hs), mean wave period, and wave direction. Observational results demonstrate that the modulation intensity is highest in Hangzhou Bay and the CRE mouth, decreasing gradually offshore. A key finding is that semidiurnal Hs maxima systematically coincide with peak flood currents and precede high water by approximately three hours. Long-term records confirm that this modulation persists year-round and intensifies during energetic events such as typhoons. The expression of the tidal signal depends on wave composition: wind-sea-dominated conditions exhibit stronger period modulation, whereas swell-dominated conditions favor coherent Hs modulation as kinematic tidal effects remain more apparent in the absence of strong local wind forcing. Numerical sensitivity experiments demonstrate that tidal currents are the primary driver of the observed wave modulation, while water-level effects are largely confined to shallow shoals. The results highlight that accurately reproducing the observed frequency–directional structure requires the inclusion of current-induced Doppler shifts and refraction. Beyond the classical following-current effects, the analysis suggests that the spatial deceleration of currents along the wave path acts as a kinematic trap that focuses wave action and sustains Hs intensification. This mechanism provides a physically plausible explanation for the observed phase relationship and points to the non-local nature of estuarine wave dynamics, where the wave state appears as an integrated response to cumulative current gradients along the propagation path. These findings emphasize the necessity of incorporating wave–current coupling in future coastal modeling and hazard forecasting.

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Salmonella virulence factor sptP activates the NLRP3/Caspase-1 pathway to induce pyroptosis and exacerbate intestinal injury in chicks - Bo Zhang; Ke Li; Hongya Yan; Rong Zhao; Zhenju Yuan; Changrui Xiao; Chengji Yang; Aiguo Xin (Veterinary Microbiology, 2026)

Haladaptatus marinus sp. nov., Haladaptatus rarus sp. nov., Haladaptatus ordinarius sp. nov., and Halomicrococcus pelagicus sp. nov., halophilic archaea from diverse coastal tidal flats - Xin-Ru Zhang; Jing Hou; Zhen Rong; Yue-Hong Wu; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Global patterns and soil controls governing terrestrial nitrogen cycling in response to experimental warming: A meta-analysis - Sen-Mao Zhang; Wan-Jia Hu; Xin-Rong Shi; Robert L. Kallenbach; Zhi-You Yuan (Soil Biology and Biochemistry, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Uncovering pH-driven metastable transitions and thermal aggregation of HMW-GSs via all-atom molecular dynamics simulations - Tao Yang; Rong-ran Zhang; Xin-rong Lv; Tian Lv; Bo Wang; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Zhe Liu; Hao Jiang (Food Hydrocolloids, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

Metabolic engineering of Pichia pastoris for high-efficiency production of branched-chain amino acids -enriched single-cell protein - Cancan Dong; Kai Hong; Fan Wu; Yanfeng Wang; Youyan Rong; Xin Wu; Jian Zhang; Le Gao (Bioresource Technology, 2026)

Waste eggshell derived porous skeleton with dual functional CNT synergistically enhance the thermal property of PCMs for thermal management - Pei Li; Yuwei Fan; Xuyan Song; Yiyi Wang; Weijian Liu; Jia Liu; Han Sun; Xin-Rong Zhang (Bioresource Technology, 2026)

Failure Behavior and Energy Evolution of Granite Containing Pre-existing Fissures Characterized by AE and DIC - Run-ze Zhang; Chuan-xin Rong; Bin Wang; Hua-qiao Xu; Yan-zhe Li; Yang Wang (Applied Geophysics, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Low-δ18O magmas at Batur, Indonesia: Evidence for slab-window melting beneath arc volcanoes - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2026)

Robust copper/mesoporous silica catalyst for efficient furfural hydrogenation to furfuryl alcohol - Xin-Yu Xiao; Jie Zhang; Rong Wang; Qi Wang; Hai-Song Li; Jing-He Yang (Biomass and Bioenergy, 2026)

Asymmetric responses of above- and below-ground traits to light and nitrogen stress in three vegetable types - Rong Liang; Ruifang Zhang; Chi Zhang; Hong Wang; Xin-Xin Wang (Plant and Soil, 2026)

Widespread incongruence in the phylogenomics of the ancient land plant lineage, Selaginellaceae (lycophytes) - Jing Zhao; Hong Yu; Carl J. Rothfels; Jian-Jun Yang; Shao-Li Fang; Zhao-Rong He; Li-Bing Zhang; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2026)

Targeted interception of membrane foulants in MBR: A straw-microplastic composite adsorbent for effective removal of oil and biopolymeric contaminants from catering wastewater - Rong Zhang; Beiyu Xin; Cong Zhang; Xiaozheng Ma; Ruoxin Wang; Jifeng Guo (Journal of Hazardous Materials, 2026)

Quantification and geological implications of manganese, barium, and copper observed by MarSCoDe LIBS at Zhurong landing site on Mars - Yuxuan Luo; Zhaopeng Chen; Jianjun Liu; Yizhong Zhang; Jingjing Zhang; Zhibin Li; Xin Ren; Xiangfeng Liu; Zhenqiang Zhang; Weiming Xu; Guolin Hu; Shaojin Han; et al. (Icarus, 2026)

Identification of a novel selenium peptide from Oryzain α hydrolysate: Selenium-specific database establishment, sequence confirmation, and molecular interaction analysis - Xin Wang; Bailiang Xue; Rong Zhang; Lin Shi; Wei Jia (Food Bioscience, 2026)

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

Defect structures of mineral surface and its influence on flotation: a critical review - Chenyang Zhang; Minsheng Fu; Xin Rao; Rong Wang; Zhipeng Tang; Sun Wei (Minerals Engineering, 2025)

Field verification of the surface renewal method for evapotranspiration measurement in arid agricultural area: The uncertainty of calibration parameter - Zhen Wang; Nanjuan Zheng; Bingbing Jiang; Yao Rong; Xin Li; Peijin Wu; Weishu Wang; Chenglong Zhang; Zailin Huo (Journal of Hydrology, 2025)

Reversing the paradigm: Oxygen-dependent switch of nTiO₂ from promoting to suppressing ARG conjugation - Jie Yu; Xin Wang; Ya-Xin Hu; Feng-Ting Cao; Qiu-Rong Zhang; Xiang-Tong Zhou; Xiang Xiao (Journal of Hazardous Materials, 2025)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

Adulteration of animal-derived whey protein in infant formula: High-throughput screening of characteristic peptides - Lin Shi; Wei Jia; Rong Zhang; Xin Wang; Haizhen Mo (Food Research International, 2025)

New insights into the growth characteristics, bacterial interaction and spoilage contribution of Pseudomonas species in vacuum skin packaged beef - Jun Yang; Ge Rong; Rongrong Liang; Lixian Zhu; Yanwei Mao; Xin Luo; Yimin Zhang; Xiaoyin Yang (Food Packaging and Shelf Life, 2025)

Dietary prebiotics combined with iron supplementation: A two-pronged approach to reduce rice cadmium bioavailability - Rong-Yue Xue; Yao-Sheng Zhang; Jin-Feng Xi; Lei Zhou; Xin-Ying Lin; Tian-Wen Ye; Yu-Hang Bao; Dongmei Zhou; Hong-Bo Li (Food and Chemical Toxicology, 2025)

Single nucleotide variations triggered responsive strip for Helicobacter pylori theranostics - Lin-Min Zhong; Qi-Ling Yang; Xin-Yi Zhong; Xiao-Rong Zhang; Fen-Ying Kong; Shan-Wen Hu; Ai-Lin Liu (Chemical Engineering Journal, 2025)

Carbonized polymer dots with conjugated core to induce dynamic interfacial protection layer formation for advanced zinc metal batteries - Jiayu Zhang; Wenchen Wang; Xiaoyan Shen; Yihan Song; Rong Li; Xin Ji; Xinyi Hu; Xiaoyu Deng; Haizhu Sun (Chemical Engineering Journal, 2025)

An injectable and programmable hydrogen delivery system for modulation tendon tissue in tendon-bone interface microenvironment - Tao Yuan; Fei Jin; Lili Qian; Xiaojiang Yang; Xin Yu; Zhongyang Lv; Ziying Sun; Shiwen Shen; Hong Qian; Jia Meng; Hui Jiang; Wenshuang Sun; et al. (Chemical Engineering Journal, 2025)

Specnuezhenide mitigates tunicamycin-induced liver injury in mice via ER stress modulation and metabolic reprogramming - Tianle Zhang; Dan Bi; Jiahui Li; Xin Jin; Huijuan Wu; Changyuan Yang; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Molecular Biology Reports, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

Analysis of the AP2/ERF transcription factor family in Eriobotrya japonica and its role in exogenous melatonin-mediated regulation of salt stress - Ling Zhu; Fuhua Liu; Xin Lin; Tianyu Fu; Lin Zou; Yuanhai Pan; Rong Zou; Yang Zhao; Hanyao Zhang (Functional & Integrative Genomics, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Copper-Induced Nephropathy: Clinical Characterization of 36 Cases and Comprehensive Literature Review - Yi-Ling Li; Jing Chen; Jin-Rong Zhang; Ting-Ting Zhou; Jian-chao Peng; Zhi-Xin Huang; Kang Nong; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Chronic dietary exposure to BDE-47 can induce inflammatory responses in the brain of common carp (Cyprinus carpio) and further trigger neurotoxicity through the 5-HT pathway - Huimin Sun; Youlian Liu; Yujie Huang; Mengbin Yuan; Zujun Ye; Rong Yang; Fuqiang Sha; Ni Tang; Bo Zhou; Defang Chen; Zhiqiong Li; Xin Zhang (Science of The Total Environment, 2025)

Field-based analysis of CO2 direct expansion heat pump systems for sustainable heating in cold regions: A case study - Yuwei Fan; Yi-Zhou Wang; Pei Li; Xiaolong Li; Jianguo Yang; Xuyan Song; Zhao-Rui Peng; Chunhua Qi; Xin-Rong Zhang (Energy and Buildings, 2025)

Multi-scale piezoresistive foam composed of graphene skeleton and vertical WS2 nanosheets designed for wearable detection/protection applications - Tengyue Song; Minxuan Xu; Yueqin Shi; Xin Li; Hang Wang; Zhe Kong; Suyu Sheng; Qi Zhang; Rong Xiang (Chemical Engineering Journal, 2025)

Deep eutectic solvent-mediated green synthesis of phosphorylated biomass adsorbents for high-efficient uranium removal from uranium tailings wastewater - Ya Wei Yang; Jie Liu; Jing Huang; Cheng Rong Zhang; Sai Jin Xiao; Xin Xin Shao; Han Wu; Li Zhang (Journal of Environmental Chemical Engineering, 2025)

DPP-IV inhibitory peptides from highland barley via machine learning and multi-scale validation - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Rong Li; Kefan Wei; Jiaqian Cao; Qingyu Zhao; Qun Shen; Yong Xue (Food Chemistry, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Correction to: Artesunate Protected Blood–Brain Barrier via Sphingosine 1 Phosphate Receptor 1/Phosphatidylinositol 3 Kinase Pathway After Subarachnoid Hemorrhage in Rats - Shilun Zuo; Hongfei Ge; Qiang Li; Xuan Zhang; Rong Hu; Shengli Hu; Xin Liu; John H. Zhang; Yujie Chen; Hua Feng (Molecular Neurobiology, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Two new steroidal saponins from the roots and rhizomes of Helleborus thibetanus - Hao Wei; Xin Zhang; Chao Ding; Yuze Li; Ziqiang Wang; Xiaomei Song; Dongdong Zhang; Rong Lin (Natural Product Research, 2025)

Counting hours or calories? Metabolic regulatory role of time-restricted eating in adults with overweight and obesity: a systematic review and meta-analysis - Xin Jin; Yan Deng; Wenxue Zhang; Xintian Xu; Shuang Rong (Critical Reviews in Food Science and Nutrition, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Corrigendum to “Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes” [J Hazard Mater 489 (2025) 137706] - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

The first set of Silurian marine red beds in South China: Spatiotemporal distribution, diachronism and paleogeographic significance - Xiaole Zhang; Jiayu Rong; Peng Tang; Renbin Zhan; Yi Wang; Zhongyang Chen; Ruiwen Zong; Bing Huang; Xin Wei (Science China Earth Sciences, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Cessation of manure application diminishes the dissemination potential of antibiotic resistance genes by altering bacterial interaction patterns in soil–lettuce systems - Ruochen Li; Xin Pei; Ming Zhang; Xuhui Deng; Chengyuan Tao; Jiabao Wang; Xueli Chen; Nicholas Clarke; Lidia Sas-Paszt; Zongzhuan Shen; Rong Li; Qirong Shen (Applied Soil Ecology, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Ultra-stable all-solid-state lithium metal batteries facilitated by in-situ LiF-rich single-ion conductor composite polymer electrolytes - Jiaze Li; Rong Yang; Aoyi Jiang; Qianwei Zhang; Xin Dong; Hongyu Shang; Yinglin Yan; Yunhua Xu; Jou-Hyeon Ahn (Chemical Engineering Journal, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

Genomic and antimicrobial resistance profiles of Clostridium perfringens isolated from pets in China - Mingjin Fang; Yuan Yuan; Xin Tian; Ying Liu; Ke Wu; Yanyan Zhu; Likun Zhang; Edward M. Fox; Ruichao Li; Li Bai; Menghan Li; Guerrino Macori; et al. (Veterinary Microbiology, 2025)

Unraveling the impact of micro- and nano-sized polymethyl methacrylate on gut microbiota and liver lipid metabolism: Insights from oral exposure studies - Peng Chen Zheng; Xin Qiang Pan; Yi Jiong Zhou; Keng Po Lai; Rong Li; Xiao Xi Zhang (Environmental Pollution, 2025)

Identification of the chemical composition of blue honeyberry leaves (Lonicera caerulea L. var. edulis) and their anti-inflammatory activity - Zhenji Rong; Chunping Yu; Xin Wang; Ruyue Wang; Yang Gao; Hailong Zhang (Medicinal Chemistry Research, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Record high CH4/N2 adsorption separation selectivity in a scalable metal-organic framework - Yan-Long Zhao; Xuefeng Bai; Xin Zhang; Zhang-Ye Han; Jian-Rong Li (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Vertical distributions of dimethyl sulfide and dimethylsulfoniopropionate and impacts of DMSP lyase and bacteria in the Yellow Sea and East China Sea - Xin-Ran Song; Qian-Yao Ma; Juan Yu; Gui-Peng Yang; Rong Chen; Zheng-Yu Zhang; Yu Jiang; Long-Fei Liu (Marine Environmental Research, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

The promotional effect of MoO3 on the CeO2/TiO2 catalyst for simultaneous removal of NO and toluene: From the insights of experimental and DFT studies - Zhuang Hu; Yi-fei Yu; Hai-yuan Zhao; Zheng-long Wu; Rong Guo; Jia-le Zhou; Xin-yue Zhou; Bing Zhang; Yang-wen Wu; Li Zhao; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Integrative deep learning framework predicts lipidomics-based investigation of preservatives on meat nutritional biomarkers and metabolic pathways - Wei Jia; Aiai Guo; Wenwen Bian; Rong Zhang; Xin Wang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Pasting, structural properties, and in vitro digestibility of water chestnut (Eleocharis dulcis Burm. f., Cyperaceae) starch co-gelatinized with different hydrocolloids - Xinyu Lv; Liyuan Rong; Weidong Zhang; Huiliang Wen; Mingyue Shen; Xin Qi; Jiajun Song; Jianhua Xie (Food Hydrocolloids, 2025)

Nonradicals-dominated peroxymonosulfate activation of g-C3N4/CeO2 floating beads for enhanced inactivation of M. aeruginosa: Performance studies and mechanistic insights - Dandan Wang; Jing Li; Rong Zhang; Beiyu Xin; Xueru Huang; Yang Wang; Jifeng Guo (Chemical Engineering Journal, 2025)

Seasonal variations in the soil microbiota of a temperate wetland in Northeast China in response to nitrogen deposition - Rong-Tao Zhang; Shen-Zheng Wang; Hai-Xiu Zhong; Xin Sui; Ying-Nan Liu (CATENA, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Machine learning discovery of novel antihypertensive peptides from highland barley protein inhibiting angiotensin I-converting enzyme (ACE) - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Yiqing Zhu; Mengyao Huo; Rong Li; Yichen Hu; Qun Shen; Yong Xue (Food Research International, 2025)

The influence of carbon dioxide on fermentation products, microbial community, and functional gene in food waste fermentation with uncontrol pH - Xin-Rong Pan; Pei-Ken Shang-Guan; Shu-Hui Li; Chu-Hao Zhang; Jia-Min Lou; Liang Guo; Lu Liu; Yin Lu (Environmental Research, 2025)

Data-driven optimization reveals the impact of Urban Heat Island effect on the retrofit potential of building envelopes - Renge Li; Chenyu Huang; Weilin Xin; Jiahong Ye; Xue Zhang; Rong Qu; Jinyu Wang; Liang Yuan; Jiawei Yao (Building and Environment, 2025)

Draft Genome of Naganishia uzbekistanensis from a Clinical Pulmonary Infection - Rong-Chen Dai; Xin-Fei Chen; Xin Fan; Li Gu; Li Zhang; Dan Guo; Ying-Chun Xu; Meng Xiao (Mycopathologia, 2025)

Consuming probiotics protects against cadmium exposure from rice consumption while promotes gut health: An assessment based on a mouse model - Jin-Feng Xi; Lei Zhou; Yao-Sheng Zhang; Xin-Ying Lin; Shan Chen; Rong-Yue Xue; Dongmei Zhou; Hong-Bo Li (Science of The Total Environment, 2025)

Prevalence and genomic characteristics of becAB-carrying Clostridium perfringens strains - Mingjin Fang; Yuan Yuan; Edward M. Fox; Ke Wu; Xin Tian; Likun Zhang; Hang Feng; Ruichao Li; Li Bai; Xinglong Wang; Zengqi Yang; Rong Zhang; et al. (Food Microbiology, 2025)

Influence of Influent Load on Nitrification/Denitrification with MBBR for Oil Shale Retorting Wastewater Treatment: Performance and Microbial Community Structure - Rong-xin Zhang; Yi Liu; Dian-nan Huang; Li Zhang; Xing-guan Ma; Peng-fei Yu; Chuang Liu; Yong-yong Wang (Water, Air, & Soil Pollution, 2025)

Amelioration impact of gut-brain communication on obesity control by regulating gut microbiota composition through the ingestion of animal-plant-derived peptides and dietary fiber: can food reward effect as a hidden regulator? - Wei Jia; Jian Peng; Yan Zhang; Jiying Zhu; Xin Qiang; Rong Zhang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2024)

Coupling polyethylene microplastics with other pollutants: Exploring their combined effects on plant health and technologies for mitigating toxicity - Linmei Cui; Rong Liang; Chi Zhang; Ruifang Zhang; Hong Wang; Xin-Xin Wang (Science of The Total Environment, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

Quantitative mechanisms for the Cd2+ adsorption increased by sewage-sludge biochar but decreased by rice-straw biochar after melamine modification - Zi-Xuan Yin; Yun-Yi Zhang; Jia-Xin Liu; Fei Huang; Qian-Jun Liu; Ming-Zhi Huang; Rong-Bo Xiao; Guo-Yi Gao; Tian-Zhen Lan; Xiao Zhou (Journal of Environmental Chemical Engineering, 2024)

Analytical model of three-dimensional concentric ellipsoidal soil arching in geosynthetic-reinforced pile-supported embankments - Rong Sun; Xin Jiang; Lei Zhang; Canyang Cui; Zhengxian Li; Yanjun Qiu (Geotextiles and Geomembranes, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

Chemical constituents from noni (Morinda citrifolia L.) fruit juice and their chemotaxonomic significance - Yu-Qin Meng; Bin Zhang; Dong-Hui Zhang; Zhang-Xin Yu; Chun-Hua Long; Si-Rong Li; Xue-Na Zhang; Xiao-Bao Li; Guang-Ying Chen (Biochemical Systematics and Ecology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Novel targets and their functions in the prognosis of uterine corpus endometrial cancer patients - Xin Sui; Penghui Feng; Jie Guo; Xingtong Chen; Rong Chen; Yanmin Zhang; Falin He; Feng Deng (Journal of Applied Genetics, 2024)

Performance of a novel annular electric field membrane bioreactor and its membrane fouling control in treating catering wastewater - Rong Zhang; Mengqian Li; Huan Ma; Yanyan Wang; Beiyu Xin; Jifeng Guo (Chemosphere, 2024)

A novel chitosan/biochar-modified eco-concrete with balanced mechanical, planting, and water purification performance for riparian restoration - Fanrun Huang; Shengxiang Rong; Shiqiang Tao; Hongqiang Chu; Huajie Huang; Shuaixiao Gao; Xin Zhang; Xinyan Xiong; Chi Zhang (Journal of Cleaner Production, 2024)

Surrogate-model-based low-carbon optimization method for tolerance allocation of mechanical components under bidirectional constraints - Rong Duan; Zhigang Jiang; Jie Yang; Xin Zeng; Hua Zhang; Xianfeng Ai (Journal of Cleaner Production, 2024)

Improving curcumin bioavailability: Targeted delivery of curcumin and loading systems in intestinal inflammation - Junyi Zhao; Wei Jia; Rong Zhang; Xin Wang; Li Zhang (Food Research International, 2024)

Investigation of isomerization and oxidation of astaxanthin in ready-to-eat Litopenaeus vannamei during accelerated storage - Na Li; Xin Fan; Yefan Wang; Kexin Zhang; Rong Liu; Yunpeng Xu; Zhifeng Tan; Wensi Xu; Dayong Zhou; Deyang Li (Food Research International, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Effects of microplastics derived from biodegradable mulch film on different plant species growth and soil properties - Rong Liang; Chi Zhang; Ruifang Zhang; Qingyun Li; Hongquan Liu; Xin-Xin Wang (Science of The Total Environment, 2024)

Structurally diverse diterpenoids from the leaves of Croton mangelong and their anti-diabetic activity - Zhi-Yong Jiang; Qi Niu; Hao-Xin Wang; Hao-Nan Xu; Hong-Xi Xie; Lin Chen; Rong Chen; Hong-Lei Zhang; Lu Gao; Ai-Xue Zuo; Hong-Ping He (Phytochemistry, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Fe-doping accelerated magnesium storage kinetics in rutile TiO2 cathode materials - Qianwei Zhang; Xin Liu; Changliang Du; Mingwei Jin; Lifen Yang; Rong Jiang; Xilan Ma; Youqi Zhu; Chuanbao Cao; Meishuai Zou (Chemical Engineering Journal, 2024)

Complete Genome Sequence of Candida mucifera from an Otitis Media Patient - Rong-Chen Dai; Jing Guan; Ya-Ting Ning; Timothy Kudinha; Wei Zhang; Xin-Fei Chen; Ge Zhang; Ying-Chun Xu; Meng Xiao (Mycopathologia, 2024)

SFRP1 reduces neutrophil infiltration and inhibits the Wnt/β-catenin pathway to alleviate oral submucous fibrosis - Rong Zhou; Lin Yin; Xin Zhang; Keke Zhu (In Vitro Cellular & Developmental Biology - Animal, 2024)

Preliminary analysis of the indicators and accumulation models of gas hydrates in the central Zhongjiannan Basin, western South China sea - Zhou-rong Cai; Xin Sui; Yong-jian Yao; Zheng-xin Yin; Xiao-dong Yang; Dong Ju; Rong-wei Zhu; Xiao-xiang Wang; Huo-dai Zhang (Marine and Petroleum Geology, 2024)

Arc building and maturation of the Lombok Island, East Sunda Arc - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Yun-Ying Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

A 3,5-dinitropyridin-2yl Substituted Flavonol-based Fluorescent Probe for Rapid Detection of H2S in Water, Foodstuff Samples and Living Cells - Lai-Xin Hong; Rong-Lan Zhang; Jian-She Zhao (Journal of Fluorescence, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

Characteristics and degradation mechanisms of polychlorinated naphthalenes in surface soil in Yangtze River Delta, China - Zherui Zhang; Guohua Zhu; Yahui Liu; Xin Zhou; Bingcheng Lin; Ziyuan Qi; Shanshan Zhang; Yueyao Yang; Xin Li; Rong Jin; Minghui Zheng (Chemosphere, 2024)

First outbreak of trypanosomiasis in farmed blood parrot cichlids (Vieja melanura♀ × Amphilophus citrinellus♂) from southern China - Jun-Yu (俊余) Zhou (周); Liwen (力文) Xu (徐); Ying-Xin (潆心) Bi (毕); Jinyong (晋勇) Zhang (章); Geoff Hide; De-Hua (德华) Lai (赖); Zhao-Rong (照荣) Lun (伦) (Aquaculture, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Multiple Applications of a Novel Fluorescence Probe with Large Stokes Shift and Sensitivity for Rapid H2S Detection - Lai-Xin Hong; Le Sun; Cong Li; Rong-Lan Zhang; Jian-She Zhao (Journal of Fluorescence, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Chemical constituents and chemotaxonomic research of the deep-sea-derived fungus Aspergillus japonicus W6 - Tong Yu; Rong Chao; Zheng-Biao Zou; Jia-Xin Duan; Kai Zhang; You Li; Ming-Min Xie; Yong Zhang; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Glutathione S-transferase directly metabolizes imidacloprid in the whitefly, Bemisia tabaci - Rong Zhang; Jing Yang; Jinyu Hu; Fengbo Yang; Jinjin Liang; Hu Xue; Xuegao Wei; Buli Fu; Mingjiao Huang; He Du; Chao Wang; Qi Su; et al. (Pesticide Biochemistry and Physiology, 2024)

Dual-edged sword effects of sulfation/hydration on Ce-doped TiO2(001) single-atom catalyst for NH3-SCR reaction: A first-principles study - Ye Jiang; Yichao Xu; Xin Sun; Guomeng Zhang; Zihan Rong; Yinsheng Jiang; Jiayao Song; Zhengda Yang (Fuel, 2024)

Building a stable and robust anti-interference DNA dissipation system by eliminating the accumulation of systemic specified errors - Luojia Wang; Wang Luo; Zhi Weng; Zhongzhong Wang; You Wu; Rong Zhao; Xiaole Han; Xin Liu; Jianhong Zhang; Yujun Yang; Guoming Xie (Analytica Chimica Acta, 2024)

In-situ GSH-responsive gas nanogenerator for active NIR-II FL/PA imaging and synergistic restoration the macrophage niche in rheumatoid arthritis - Xiaochun Zheng; Weiwei Kang; Yarong Jin; Xin Zhang; Wenxuan Wang; Dongsheng Li; Shutong Wu; Lin Chen; Shichao Meng; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Fine-grained PM 2 . 5 prediction in Lanzhou based on the spatiotemporal graph convolutional network - Qiang Zhang; Xin Yu; Rong Guo; Yibin Qiao; Ying Qi (Atmospheric Pollution Research, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

Effects of zinc oxide nanocomposites on microorganism growth and protection of physicochemical quality during maize storage - Dong-Dong Zhang; Jin-Feng Zhao; Li-Qin Tan; Qiong Wu; Hao-Xin Lv; Yu-Rong Zhang; Min Zhang (International Journal of Food Microbiology, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Interplanting leguminous shrubs boosts the trophic interactions of soil micro-food web in a karst grassland - Jiachen Wang; Jie Zhao; Rong Yang; Xin Liu; Xuyuan Zhang; Wei Zhang; Xiaoyong Chen; Wende Yan; Kelin Wang (Soil Biology and Biochemistry, 2024)

An appropriate amount of straw replaced chemical fertilizers returning reduced net greenhouse gas emissions and improved net ecological economic benefits - Lian Zhang; Guoliang Jiang; Rusheng Xiao; Kun Hou; Xin Liu; Xinyu Liu; Pei Yuan; Feng Tian; Lichu Yin; Hongmei Zhu; Chang Tian; Lan Yang; et al. (Journal of Cleaner Production, 2024)

Stability analysis of unsaturated soil slopes with cracks under rainfall infiltration conditions - Lei Zhang; Xin Jiang; Rong Sun; Hanyan Gu; Yongguo Fu; Yanjun Qiu (Computers and Geotechnics, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

An independent framework-based evapotranspiration model (IFEM) for dual-source: From field to regional scale - Shuai Wang; Chaozi Wang; Chenglong Zhang; Weishu Wang; Pu Wang; Xin Zhang; Xingwang Wang; Yao Rong; Di Wang; Guanhua Huang; Zailin Huo (Remote Sensing of Environment, 2023)

Exploring novel ANGICon-EIPs through ameliorated peptidomics techniques: Can deep learning strategies as a core breakthrough in peptide structure and function prediction? - Wei Jia; Jian Peng; Yan Zhang; Jiying Zhu; Xin Qiang; Rong Zhang; Lin Shi (Food Research International, 2023)

Experimental investigation of wave attenuation by mangrove forests with submerged canopies - Rong Zhang; Yongping Chen; Jiaxin Lei; Xin Zhou; Peng Yao; Marcel J.F. Stive (Coastal Engineering, 2023)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

First principles insights into the interaction mechanism of iron doped thermally activated kaolinite with Cd and Pb pollutants in organic solid waste incineration flue gas - Yang-wen Wu; Rong Guo; Li-juan Sun; Xin-yue Zhou; Jia-le Zhou; Hai-yuan Zhao; Yi-fei Yu; Zhuang Hu; Bin Hu; Ji Liu; Bing Zhang; Li Zhao; et al. (Waste Management, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Mesoscopic measurement of damage and shear bands of granite residual soil using Micro-CT and digital volume correlation - Cheng-sheng Li; Bing-xin Zhang; Zhi-jun Liu; Ling-wei Kong; Rong-jun Shu (Journal of Mountain Science, 2023)

Multifunctional dumbbell probes-based logic circuits: microRNAs logic detection and tumor cells identification - Xin Liu; Baiying Li; Qian Liu; Li Zhang; Rong Zhao; Di Wu; Luojia Wang; Zhongzhong Wang; Guoming Xie; Wenli Feng (Analytica Chimica Acta, 2023)

N, N-bis (2-hydroxyethyl) malonamide based amidoxime functionalized polymer immobilized in biomembranes for highly selective adsorption of uranium(VI) - Yang Li; Ze-Yang Wang; Qi Ren; Feng Zhang; Xu-Xin Li; Qiang Wu; Rong Hua; Ze-Yi Yan; Yun Wang (Chemosphere, 2023)

Application of super-cooled storage of aquatic products: A review - Xin-Yu Liu; Xue-Lai Zhang; Guan-Bang Wang; Fan-Yang Mo; Xin-Rong Zhang (International Journal of Refrigeration, 2023)

Experimental study on visualization of TBAB hydrate formation in confined small channels - Qi-Rong Zuo; Ming Gao; Peng Kong; Li-Xin Zhang (Fuel, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Research progress of electrically-enhanced membrane bioreactor (EMBR) in pollutants removal and membrane fouling alleviation - Rong Zhang; Liying Hao; Kai Cheng; Beiyu Xin; Junqi Sun; Jifeng Guo (Chemosphere, 2023)

Method for quantitative extraction of copper hydroxide nanoparticles from farmland soil - Xin-Yuan Li; Yuan Yang; Peng Huang; Ying-Rong Wang; Yu-Lin Nie; Li Zhang; Qiang Wang (Science of The Total Environment, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

A deep spatio-temporal learning network for continuous citywide air quality forecast based on dense monitoring data - Rong Guo; Qiang Zhang; Xin Yu; Ying Qi; Bu Zhao (Journal of Cleaner Production, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

COVID-19 related antiviral drugs are less adsorbable on sediment under alkaline and high cation conditions - Xin Xu; Rong Zhu; Yun Zhang; Shannon L. Bartelt-Hunt; Hua Zou; Chen Chen (Science of The Total Environment, 2023)

Effect of flue gas components on the removal of cadmium pollutants by transition metal-modified activated carbon: Density functional theory and thermodynamic study - Xin-Yue Zhou; Jia-Le Zhou; Rong Guo; Yin-jie Liu; Yi-fei Yu; Bing Zhang; Yang-Wen Wu; Li Zhao; Qiang Lu (Fuel, 2023)

Ectopic over-expression of HaFT-1, a 14-3-3 protein from Haloxylon ammodendron, enhances acquired thermotolerance in transgenic Arabidopsis - Rong Pan; Wenjing Ren; Shuanshuan Liu; Hua Zhang; Xin Deng; Bo Wang (Plant Molecular Biology, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Four anti-inflammatory aromadendrane sesquiterpenoid fucosides and other constituents from Pittosporum glabratum var. neriifolium - Bai-Tong Sha; Rong Huang; Qiang-Guo Zhang; Sheng-Nan Guan; Jia-Qi Ding; Xin-Zheng Liu; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

BPA exposure enhances the metastatic aggression of ovarian cancer through the ERα/AKT/mTOR/HIF-1α signaling axis - Xin Xie; Yan Zhu; Huimin Cheng; Haili Li; Yadi Zhang; Rong Wang; Wenyong Li; Fengrui Wu (Food and Chemical Toxicology, 2023)

Dispersed Pd/alumina catalyst with finite iodine entry for boosted CO purification and dimethyl carbonate synthesis - Yun-Yun Zeng; Lu-Yang Qiao; Shan-Shan Zong; Rong Guo; Jian-Kai Cheng; Xin-Yi Cao; Zhang-Feng Zhou; Mao-Hong Fan; Yuan-Gen Yao (Chemical Engineering Journal, 2023)

Molecular Hydrogen Mediates Neurorestorative Effects After Stroke in Diabetic Rats: the TLR4/NF-κB Inflammatory Pathway - Wan-Chao Yang; Ting-ting Li; Qiang Wan; Xin Zhang; Li-Ying Sun; Yu-Rong Zhang; Pei-Chen Lai; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)
Diabetes is an independent risk factor for stroke and amplifies inflammation. Diabetic stroke is associated with a higher risk of death and worse neural function. The identification of effective anti-inflammatory molecules with translational advantages is particularly important to promote perioperative neurorestorative effects. Applying molecular hydrogen, we measured blood glucose levels before and after middle cerebral artery occlusion (MCAO), 48-h cerebral oedema and infarct volumes, as well as 28-day weight, survival and neurological function. We also measured the levels of TLR4, NF-κB p65, phosphorylated NF-κB p65, catecholamines, acetylcholine and inflammatory factors. All measurements comprehensively showed the positive effect and translational advantage of molecular hydrogen on diabetic stroke. Molecular hydrogen improved the weight, survival and long-term neurological function of rats with diabetic stroke and alleviated changes in blood glucose levels before and after middle cerebral artery occlusion (MCAO), but no difference in circadian rhythm was observed. Molecular hydrogen inhibited the phosphorylation of NF-κB and significantly reduced inflammation. Molecular hydrogen mediates neurorestorative effects after stroke in diabetic rats. The effect is independent of circadian rhythms, indicating translational advantages. The molecular mechanism is related to the TLR4/NF-κB pathway and inflammation. Graphical abstract Molecular hydrogen (H 2 ) affects outcomes of ischemic stroke with diabetes mellitus (DM).

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Grass harvesting eliminates the beneficial effects of legume addition on soil nematode communities in a tall grass pasture - Jie Zhao; Wei Zhang; Xin Liu; Rong Yang; Dan Xiao; Xunyang He; Kelin Wang (Agriculture, Ecosystems & Environment, 2023)

Molecular detection and characterization of three novel parvoviruses belonging to two different subfamilies in zoo birds - Yan Wang; Yijie Sun; Xin Li; Rong Chen; Wang Li; Li Ji; Qifan Zhao; Likai Ji; Shixing Yang; Wen Zhang (Archives of Virology, 2023)

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

Screening of pesticides in serum, urine and cerebrospinal fluid collected from an urban population in China - Ke-Xin Zhao; Ming-Yan Zhang; Dan Yang; Rong-Shu Zhu; Zi-Feng Zhang; Ying-Hua Hu; Kurunthachalam Kannan (Journal of Hazardous Materials, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Effects of vegetation type differences induced by human disturbance on the nutrition strategy and gut microbiota of Siberian roe deer - Zi‐ao Yuan; Lin‐qiang Zhong; Hai‐rong Du; Jia‐nan Feng; Xin‐xin Liu; Hong‐yi Yuan; Jin‐hao Guo; Peng Liu; Ming‐hai Zhang (Molecular Ecology, 2023)
The Siberian roe deer ( Capreolus pygargus ) is a widely distributed ungulate in northeast China. Due to a series of human disturbance activities such as large‐scale forest cutting, deforestation and reclamation, road construction in the past, the appearance and internal structure of forest vegetation in the habitat of Siberian roe have changed significantly. At the same time, Siberian roe population had a series of ecological adaptation responses in the face of such habitat changes. Therefore, two typical vegetation types with differences were selected in the Muling Forest, China. We used nutritional ecology and microbial metagenomic analysis techniques to compare the nutritional selection strategy and the structure and functional characteristics of faecal microbiota of Siberian roe groups in two vegetation types. The results showed that the α diversity of dietary and gut microbes of deer in Natural Forest was higher than that in Plantation Forest. However, the gut microbes of the Plantation Forest group contained more unique enzymes in the functional pathways of carbon metabolism and biosynthesis of amino acids. This study suggests that habitat type is associated with plant community composition, and contributes to changes in the intake proportions of major macronutrients by altering the availability, quality, and composition of certain edible plants. Feeding behaviour may be an important regulatory factor of gut microbiota structure and function of deer. The metabolic function of gut microbiota to different nutrients may affect the microbial community structure. Therefore, our results suggest that the gut microbes of Siberian roe may have coevolved with their diets, and reflect the adaptability of deer populations to environmental changes (e.g., vegetation type). Our study provides new insights into how spatial heterogeneity affects nutrition and microecosystems by describing the interactions among the environment, diet, and symbiotic gut microbes in wild ungulates.

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

The loss of Halloween gene function seriously affects the development and reproduction of Diaphorina citri (Hemiptera: Liviidae) and increases its susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Jing Wang; Tian-Rong Xin; Zhi-Wen Zou; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Formation of RNA adducts resulting from metabolic activation of spice ingredient safrole mediated by P450 enzymes and sulfotransferases - Xin Wang; Guangyun Ran; Yufen Liao; Bowen Gong; Chutian Wu; Rong Tan; Ying Liu; Shiyu Zhang; Ying Peng; Weiwei Li; Jiang Zheng (Food and Chemical Toxicology, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Characterizing the obesogenic and fatty liver-inducing effects of Acetyl tributyl citrate (ATBC) plasticizer using both in vivo and in vitro models - Weigao Zhang; Jiapeng Jie; Qian Xu; Rong Wei; Xin Liao; Danyang Zhang; Yayun Zhang; Jianfa Zhang; Guanyong Su; Yuxin Chen; Dan Weng (Journal of Hazardous Materials, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Spinal cord astrocyte P2X7Rs mediate the inhibitory effect of electroacupuncture on visceral hypersensitivity of rat with irritable bowel syndrome - Zhi-jun Weng; Shi-xiu Hu; Fang Zhang; Zhi-ying Zhang; Yun Zhou; Min Zhao; Yan Huang; Yu-hu Xin; Huan-gan Wu; Hui-rong Liu (Purinergic Signalling, 2023)

Ex vivo coronary endothelial cell activation associated with indoor coal combustion initiated atherosclerosis - Wanjun Zhang; Yaxian Pang; Wenting Cheng; Tao Wang; Yanting Li; Xin Li; Jianzhong Zhang; Xiaowen Xia; Yuxin Zheng; Rong Zhang; Jinglong Tang (Science of The Total Environment, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

Four new glycosides from Gerbera piloselloides - Ha Gao; Chen-Xu Zhao; Xin-Yao Luo; Jing-Rong Li; Xiao-Chuan Ye; Tao Zhang; Zhong-Mei Zou (Phytochemistry Letters, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

Characteristics of rural sewage discharge and a case study on optimal operation of rural sewage treatment plant in Shaanxi, China - Yi Rong; Yang Zhang; Zenghui Sun; Zhe Liu; Xin Jin; Pengkang Jin (Chemical Engineering Journal, 2023)

Community succession of microbial populations related to C N P S biological transformations regulates product maturity during cow-manure-driven composting - Xin Liu; Xiangmin Rong; Junyan Yang; Han Li; Wang Hu; Yong Yang; Guoliang Jiang; Rusheng Xiao; Xingxiang Deng; Guixian Xie; Gongwen Luo; Jiachao Zhang (Bioresource Technology, 2023)

An integrated process for co-producing fermentable sugars and xylonate from sugarcane bagasse based on xylonic acid assisted pretreatment - Zhen Zhu; Rong Huang; Shuangquan Yao; Yiruo Liu; Qibo Zhang; Xin Zhou; Kankan Jiang (Bioresource Technology, 2023)

Impacts of tidal flat reclamation on suspended sediment dynamics in the tidal-dominated Wenzhou Coast, China - Rong Zhang; Yongping Chen; Peixiong Chen; Xin Zhou; Biying Wu; Kehao Chen; Zhilin Sun; Peng Yao (Frontiers in Marine Science, 2023)
Reclamation of tidal flats is one of the engineering measures of expanding land area and developing the economy in coastal areas; however, this process disturbs the natural processes of the tidal flat system. Taking the flood-tidal dominant Oufei tidal flat at the Wenzhou coast as a study area, the influences of tidal flat reclamation on tidal and suspended sediment dynamics were comprehensively investigated via numerical modeling. Before the reclamation, the Eulerian residual current flows alongshore and the residual sediment transport on-shore in the tidal flat area. The reclamation reduces the tidal flat area, shifting the M4 co-phase line toward the coast and squeezing the flood-dominated area. Consequently, the tidal current is weakened and the suspended sediment concentration (SSC) is reduced, but the residual sediment transport change insignificantly. The residual sediment transport in the Feiyunjiang Estuary is controlled by the tidal pumping effect. The upper estuary shows a net sediment transport landward, while a seaward transport is observed in the lower estuary, which further splits into two circulation outside the estuary. The south Oufei dike construction interferes the northern sediment circulation, resulting in the alteration of local SSC and enhancing landward sediment transport inside the estuary. The methodology and understandings arising from this study could be a good reference for the analysis of suspended sediment transport under tidal flat reclamation effects at other sites.

Nondestructive and rapid method for sex identification of the tropical sea cucumber Holothuria scabra by anal swab sampling - Zixuan E; Chuhang Cheng; Feifei Wu; Chunhua Ren; Rong Chen; Yingzhu Rao; Bo Ma; Xiao Jiang; Peng Luo; Xiaomin Li; Xin Zhang; Fajun Jiang; et al. (Aquaculture, 2023)

A study on the correlation between intrauterine microbiota and uterine pyogenesis in dogs - Hui-Hua Zheng; Chong-Tao Du; Yu-Zhu Zhang; Chao Yu; Rong-Lei Huang; Xin-Yue Tang; Guang-Hong Xie (Theriogenology, 2023)

Efficient synthesis of PdIr nanocatalysts with controllable surface composition for electrochemical oxidation of methanol - Ce Fu; Pan Wang; Rong-Hua Zhang; Luo-Yi Yan; Zheng Cheng; Xin Zhang; Xin-Wen Zhou (Fuel, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Dysregulation of Circulatory Levels of lncRNAs in Parkinson’s Disease - Ting Huang; Jin-Ying Zhao; Rong-Rong Pan; Teng Jiang; Xin-Xin Fu; Qing Huang; Xi-Xi Wang; Peng-Yu Gong; You-Yong Tian; Ying-Dong Zhang (Molecular Neurobiology, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

QNE1 is a key flowering regulator determining the length of the vegetative period in soybean cultivars - Zhengjun Xia; Hong Zhai; Yanfeng Zhang; Yaying Wang; Lu Wang; Kun Xu; Hongyan Wu; Jinglong Zhu; Shuang Jiao; Zhao Wan; Xiaobin Zhu; Yi Gao; et al. (Science China Life Sciences, 2022)

Manganese addition accelerates litter decomposition and alters litter mixing effects in the late stage in subtropical plantations of southern China - Pan-Pan Wu; Ling-Xin Jiang; Yan Zhang; Qi-Han Tu; Rong Mao (Plant and Soil, 2022)

Characteristics of antibiotic resistance gene distribution in rainfall runoff and combined sewer overflow - Xin-rong Pan; Lei Chen; Li-ping Zhang; Jian-e Zuo (Environmental Science and Pollution Research, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Homozygous missense mutation in CCDC155 disrupts the transmembrane distribution of CCDC155 and SUN1, resulting in non-obstructive azoospermia and premature ovarian insufficiency in humans - Huan Wu; Xin Zhang; Rong Hua; Yuqian Li; Li Cheng; Kuokuo Li; Yiyuan Liu; Yang Gao; Qunshan Shen; Guanxiong Wang; Mingrong Lv; Yuping Xu; et al. (Human Genetics, 2022)

Cortical connectivity gradients and local timescales during cognitive states are modulated by cognitive loads - Heming Zhang; Rong Zhao; Xin Hu; Sihai Guan; Daniel S. Margulies; Chun Meng; Bharat B. Biswal (Brain Structure and Function, 2022)

Prediction model for disc cutter wear during hard rock breaking based on plastic removal abrasiveness mechanism - Lei She; She-rong Zhang; Chao Wang; Zheng-qiao Wu; Lun-chuang Yu; Li-xin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

Experimental Investigation on Behavior of Single-Helix Anchor in Sand Subjected to Uplift Cyclic Loading - Dongxue Hao; Jianyi Che; Rong Chen; Xin Zhang; Chi Yuan; Xichao Chen (Journal of Marine Science and Engineering, 2022)
Helical anchors have been widely used in geotechnical engineering due to their large uplift resistance. However, the current knowledge of the cyclic performance of helical anchors is still insufficient. Consequently, a series of small-scale model tests are carried out in sand to investigate the influences of embedment ratio, sand compactness and the cyclic parameters on the monotonic, cyclic and post-cyclic performance of single-helix anchors. The tests results indicate that the single-helix anchors with optimal embedment ratio still exhibit a relatively high uplift capacity after suffering cyclic load. The cyclic frequency has the greatest influence on the accumulated displacement, and the influence of amplitude is relatively greater than that of the mean cyclic load. The anchors in dense sand exhibit better performance to resist pullout than those in medium–dense sand under the same cyclic parameter ratios. Moreover, the correlation of post-cyclic uplift capacity and displacement after cyclic loading as well as the possible influence of the upward displacement on the sand flow above the helix are discussed.

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Correction to: Higher sequestration of wheat versus maize crop carbon in soil under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Comment on “Relationship of Circulating Copper Level with Gestational Diabetes Mellitus: a Meta-analysis and Systemic Review” - Shu-ping Li; Xiao-ping Zhang; Xin-hong Cui; Li-juan Zhao; Yan-jun Rong (Biological Trace Element Research, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Neiella holothuriorum sp. nov., isolated from the gut of a sea cucumber Apostichopus japonicus - Xin-Feng Bai; Xue-Lian Lv; Xue Liu; Ting-Ting Cui; Mian-Song Zhang; Ning Ding; Chang-Heng Liu; Ai-Rong Jia (Antonie van Leeuwenhoek, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Higher sequestration of wheat versus maize crop carbon in soils under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Mechanisms of soil organic carbon stability and its response to no‐till: A global synthesis and perspective - Zheng‐Rong Kan; Wen‐Xuan Liu; Wen‐Sheng Liu; Rattan Lal; Yash Pal Dang; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2022)
Mechanisms of soil organic carbon (SOC) stabilization have been widely studied due to their relevance in the global carbon cycle. No‐till (NT) has been frequently adopted to sequester SOC; however, limited information is available regarding whether sequestered SOC will be stabilized for long term. Thus, we reviewed the mechanisms affecting SOC stability in NT systems, including the priming effects (PE), molecular structure of SOC, aggregate protection, association with soil minerals, microbial properties, and environmental effects. Although a more steady‐state molecular structure of SOC is observed in NT compared with conventional tillage (CT), SOC stability may depend more on physical and chemical protection. On average, NT improves macro‐aggregation by 32.7%, and lowers SOC mineralization in macro‐aggregates compared with CT. Chemical protection is also important due to the direct adsorption of organic molecules and the enhancement of aggregation by soil minerals. Higher microbial activity in NT could also produce binding agents to promote aggregation and the formation of metal‐oxidant organic complexes. Thus, microbial residues could be stabilized in soils over the long term through their attachment to mineral surfaces and entrapment of aggregates under NT. On average, NT reduces SOC mineralization by 18.8% and PE intensities after fresh carbon inputs by 21.0% compared with CT ( p Q 10 ) is observed in NT due to greater Q 10 in macro‐aggregates, an increase of soil moisture regime in NT could potentially constrain the improvement of Q 10 . This review improves process‐based understanding of the physical and chemical mechanism of protection that can act, independently or interactively, to enhance SOC preservation. It is concluded that SOC sequestered in NT systems is likely to be stabilized over the long term.

Caffeine Inhibits Activation of the NLRP3 Inflammasome via Autophagy to Attenuate Microglia-Mediated Neuroinflammation in Experimental Autoimmune Encephalomyelitis - Hui-Qi Wang; Kai-Yi Song; Jin-Zhou Feng; Si-Yuan Huang; Xiu-Ming Guo; Lei Zhang; Gang Zhang; Ying-Chao Huo; Rong-Rong Zhang; Yue Ma; Qing-Zhe Hu; Xin-Yue Qin (Journal of Molecular Neuroscience, 2022)

Promotional effect of ZrO2 and WO3 on bimetallic Pt-Pd diesel oxidation catalyst - Rongrong Fan; Zhaoqiang Li; Yu Wang; Yan Wang; Zhiyong Ding; Cheng Zhang; Na Kang; Xin Guo; Rong Wang (Environmental Science and Pollution Research, 2022)

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Biomechanical Strengthening Design for Limb Articulation Based on Reconstructed Skeleton Kinesthetics - Jing-Hua Xu; Zheng-Xin Tu; Jing-Xuan Xu; Shu-You Zhang; Jian-Rong Tan (Journal of Medical and Biological Engineering, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Triaxial Compression Testing at Constant and Reducing Confining Pressure for the Mechanical Characterization of a Specific Type of Sandstone - Jiu-chang Zhang; Zhi-nan Lin; Bo Dong; Rong-xin Guo (Rock Mechanics and Rock Engineering, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Effect of bFGF on fibroblasts derived from the golden snub-nosed monkey - Xin Liu; Hao Wei; Jing Yang; Jingjing Li; Pei Zhang; Yuli Li; Rong Hou; Jinlian Hua; Xingrong Yan; Baoguo Li (Primates, 2021)

The CMIP6 Historical Simulation Datasets Produced by the Climate System Model CAMS-CSM - Xinyao Rong; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua; Zhengqiu Zhang; Yufei Xin (Advances in Atmospheric Sciences, 2021)
This paper describes the historical simulations produced by the Chinese Academy of Meteorological Sciences (CAMS) climate system model (CAMS-CSM), which are contributing to phase 6 of the Coupled Model Intercomparison Project (CMIP6). The model description, experiment design and model outputs are presented. Three members’ historical experiments are conducted by CAMS-CSM, with two members starting from different initial conditions, and one excluding the stratospheric aerosol to identify the effect of volcanic eruptions. The outputs of the historical experiments are also validated using observational data. It is found that the model can reproduce the climatological mean states and seasonal cycle of the major climate system quantities, including the surface air temperature, precipitation, and the equatorial thermocline. The long-term trend of air temperature and precipitation is also reasonably captured by CAMS-CSM. There are still some biases in the model that need further improvement. This paper can help the users to better understand the performance and the datasets of CAMS-CSM.

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Habitat fragmentation changes top‐down and bottom‐up controls of food webs - Rong Wang; Xin Zhang; Yi‐Su Shi; Yuan‐Yuan Li; Jianguo Wu; Fangliang He; Xiao‐Yong Chen (Ecology, 2020)
Top‐down and bottom‐up controls regulate the structure and stability of ecosystems, but their relative roles in terrestrial systems have been debated. Here we studied a hydro‐inundated land‐bridge system in subtropical China and tested the relative importance of these two controls in determining the rodent‐mediated regeneration of a locally dominant tree species. Our results showed that both controls operated in terrestrial habitats and that their relative importance switched as habitat size changed. Habitat loss initially removed predators of rodents that released rodent populations and triggered massive seed predation (top‐down control), leading to reduced seedling establishment. A further reduction in habitat size led to decrease in rodent population that was supposed to increase seedling survival of the tree species, but the decline in habitat size deteriorated the abiotic environments (bottom‐up control) that severely prevented seedling recruitment. As the ongoing global land use change is creating increasing number of small‐sized forest fragments, our findings provide novel insights into the restoration of seriously fragmented forests.

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Critical regulation of atherosclerosis by the KCa3.1 channel and the retargeting of this therapeutic target in in-stent neoatherosclerosis - Yan-Rong Zhu; Xiao-Xin Jiang; Dai-Min Zhang (Journal of Molecular Medicine, 2019)

Relationship between genetic variation in the α2A-adrenergic receptor and the cardiovascular effects of dexmedetomidine in the Chinese Han population - Shao-jun Zhu; Kui-rong Wang; Xiong-xin Zhang; Sheng-mei Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

Arbuscular mycorrhizal fungi abundance was sensitive to nitrogen addition but diversity was sensitive to phosphorus addition in karst ecosystems - Dan Xiao; Rongxiao Che; Xin Liu; Yongjun Tan; Rong Yang; Wei Zhang; Xunyang He; Zhihong Xu; Kelin Wang (Biology and Fertility of Soils, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

A study of the characteristics of energy flux and its relationship with the summer monsoon over alpine wetlands in the source region of the Yellow River - Dongyu Jia; Jun Wen; Yaoming Ma; Juan Zhou; Jinlei Chen; Rong Liu; Xin Wang; Tangtang Zhang; Xin Lai; ZuoLiang Wang (Meteorology and Atmospheric Physics, 2019)

Coupling the Common Land Model to ECHAM5 Atmospheric General Circulation Model - Yufei Xin; Yongjiu Dai; Jian Li; Xinyao Rong; Guo Zhang (Journal of Meteorological Research, 2019)

A B-box zinc finger protein, MdBBX10, enhanced salt and drought stresses tolerance in Arabidopsis - Xin Liu; Rong Li; Yaqing Dai; Li Yuan; Qinghua Sun; Shizhong Zhang; Xiaoyun Wang (Plant Molecular Biology, 2019)

Silurian integrative stratigraphy and timescale of China - Jiayu Rong; Yi Wang; Renbin Zhan; Junxuan Fan; Bing Huang; Peng Tang; Yue Li; Xiaole Zhang; Rongchang Wu; Guangxu Wang; Xin Wei (Science China Earth Sciences, 2019)

The CAMS Climate System Model and a Basic Evaluation of Its Climatology and Climate Variability Simulation - Xinyao Rong; Jian Li; Haoming Chen; Yufei Xin; Jingzhi Su; Lijuan Hua; Tianjun Zhou; Yanjun Qi; Zhengqiu Zhang; Guo Zhang; Jianduo Li (Journal of Meteorological Research, 2018)

An Assessment of CAMS-CSM in Simulating Land–Atmosphere Heat and Water Exchanges - Guo Zhang; Jianduo Li; Xinyao Rong; Yufei Xin; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua (Journal of Meteorological Research, 2018)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

The warm season characteristics of the turbulence structure and transfer of turbulent kinetic energy over alpine wetlands at the source of the Yellow River - Dongyu Jia; Jun Wen; Yaoming Ma; Xin Wang; Tangtang Zhang; Rong Liu; Xin Lai (Meteorology and Atmospheric Physics, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Hydrological response of biological soil crusts to global warming: A ten‐year simulative study - Xin‐Rong Li; Rong‐Liang Jia; Zhi‐Shan Zhang; Peng Zhang; Rong Hui (Global Change Biology, 2018)
Biological soil crusts across the desert regions play a key role in regional ecological security and ecological health. They are vital biotic components of desert ecosystems that maintain soil stability, fix carbon and nitrogen, influence the establishment of vascular plants, and serve as habitats for a large number of arthropods and microorganisms, as well as influencing soil hydrological processes. Changes in temperature and precipitation are expected to influence the functioning of desert ecosystems by altering biotic components such as the species composition of biological soil crusts. However, it remains unclear how these important components will respond to the prolonged warming and reduced precipitation that is predicted to occur with climate change. To evaluate how the hydrological properties of these biological soil crusts respond to these alterations, we used open‐top chambers over a 10‐year period to simulate warming and reduced precipitation. Infiltration, dew entrapment, and evaporation were measured as surrogates of the hydrological functioning of biological soil crusts. It was found that the ongoing warming coupled with reduced precipitation will more strongly affect moss in crustal communities than lichens and cyanobacteria, which will lead to a direct alteration of the hydrological performance of biological soil crusts. Reductions in moss abundance, surface cover, and biomass resulted in a change in structure and function of crustal communities, decreased dew entrapment, and increased infiltration and evaporation of biological soil crusts in desert ecosystems, which further impacted on the desert soil water balance.

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

Effects of simvastatin on the function of splenic CD4+ and CD8+ T cells in sepsis mice - Bingbing Kong; Xiaofeng Wang; Wenping Yang; Xin Zhao; Rong Zhang; Yu Wang (Immunologic Research, 2018)

Detrital apatite fission track constraints on Cenozoic tectonic evolution of the northeastern Qinghai-Tibet Plateau, China: Evidence from Cenozoic strata in Lulehe section, Northern Qaidam Basin - Ding-ding Du; Cheng-jun Zhang; Muhammad Saleem Mughal; Xiao-yu Wang; Dembele Blaise; Jun-ping Gao; Yuan Ma; Xin-rong Luo (Journal of Mountain Science, 2018)

Differential Inhibition of Nav1.7 and Neuropathic Pain by Hybridoma-Produced and Recombinant Monoclonal Antibodies that Target Nav1.7 - Sangsu Bang; Jiho Yoo; Xingrui Gong; Di Liu; Qingjian Han; Xin Luo; Wonseok Chang; Gang Chen; Sang-Taek Im; Yong Ho Kim; Judith A. Strong; Ma-Zhong Zhang; et al. (Neuroscience Bulletin, 2018)

p70S6K activation promotes the transdifferentiation of fibroblasts to myofibroblasts in pterygium tissue growth on the cornea - Xin-Rong Zhao; Ming-Chang Zhang; Hua-Tao Xie; Nan Ji; Le-Tian Sun (Biotechnology Letters, 2018)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Artesunate Protected Blood–Brain Barrier via Sphingosine 1 Phosphate Receptor 1/Phosphatidylinositol 3 Kinase Pathway After Subarachnoid Hemorrhage in Rats - Shilun Zuo; Hongfei Ge; Qiang Li; Xuan Zhang; Rong Hu; Shengli Hu; Xin Liu; John H. Zhang; Yujie Chen; Hua Feng (Molecular Neurobiology, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Effects of Litter Evenness, Nitrogen Enrichment and Temperature on Short-Term Litter Decomposition in Freshwater Marshes of Northeast China - Xin-Hou Zhang; Xiao-Xin Sun; Rong Mao (Wetlands, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Slow-release nitrogen fertilizers can improve yield and reduce Cd concentration in pakchoi (Brassica chinensis L.) grown in Cd-contaminated soil - Ran-Ran Zhang; Yue Liu; Wan-Lei Xue; Rong-Xin Chen; Shao-Ting Du; Chong-Wei Jin (Environmental Science and Pollution Research, 2016)

Genome-wide analysis of Gro/Tup1 family corepressors and their responses to hormones and abiotic stresses in maize - Hongyou Li; Kaifeng Huang; Hanmei Du; Hongling Wang; Xin Chen; Shibin Gao; Hailan Liu; Moju Cao; Yanli Lu; Tingzhao Rong; Suzhi Zhang (Journal of Plant Biology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Amycolatopsis xuchangensis sp. nov. and Amycolatopsis jiguanensis sp. nov., isolated from soil - Jian-Rong Huang; Hong Ming; Shuai Li; Zhuo-Li Zhao; Xiao-Lin Meng; Jian-Xin Zhang; Zhong Tang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

DNA-Binding, Photocleavage, and Photodynamic Anti-cancer Activities of Pyridyl Corroles - Zhen-Hua Liang; Hai-Yang Liu; Rong Zhou; Zao Zhang; Atif Ali; Bing-Jie Han; Yun-Jun Liu; Xin-Yan Xiao (The Journal of Membrane Biology, 2016)

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

Evaluation of the major royal jelly proteins as an alternative to fetal bovine serum in culturing human cell lines - Di Chen; Xiao-xuan Xin; Hao-cheng Qian; Zhang-yin Yu; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Composition of phosphorus in wetland soils determined by SMT and solution 31P-NMR analyses - Wenqiang Zhang; Xin Jin; Yuekui Ding; Xiaolei Zhu; Nan Rong; Jie Li; Baoqing Shan (Environmental Science and Pollution Research, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Phosphorus speciation of sediments from lakes of different tropic status in Eastern China - Wenqiang Zhang; Nan Rong; Xin Jin; Jie Li; Yuekui Ding; Xiaolei Zhu; Baoqing Shan (Environmental Science and Pollution Research, 2016)

Preparation of Bacterial Cellulose/Inorganic Gel of Bentonite Composite by In Situ Modification - Bo Wang; Gao-xiang Qi; Chao Huang; Xiao-Yan Yang; Hai-Rong Zhang; Jun Luo; Xue-Fang Chen; Lian Xiong; Xin-De Chen (Indian Journal of Microbiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Age-related changes in photosynthesis and water relations of revegetated Caragana korshinskii in the Tengger desert, Northern China - Jing-Ting Bao; Jin Wang; Xin-Rong Li; Zhi-Shan Zhang; Jie-Qiong Su (Trees, 2015)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

The anti-angiogenic role of discoidin domain receptor 2 (DDR2) in laser-induced choroidal neovascularization - Tong Zhu; Jie Zhu; Xin Bu; Hu Zhao; Shuya Zhang; Yuan Chang; Rong Li; Libo Yao; Yusheng Wang; Jin Su (Journal of Molecular Medicine, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

An improved SCGM(1,m) model for multi-point deformation analysis - Qi-jie Wang; Chang-cheng Wang; Rong-an Xie; Xin-qing Zhang; Jian-jun Zhu (Geosciences Journal, 2014)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Exogenous hydrogen peroxide enhanced the thermotolerance of Festuca arundinacea and Lolium perenne by increasing the antioxidative capacity - Yan Wang; Jie Zhang; Jian-Long Li; Xin-Rong Ma (Acta Physiologiae Plantarum, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Heavy metal and organic contaminants in mangrove ecosystems of China: a review - Zai-Wang Zhang; Xiang-Rong Xu; Yu-Xin Sun; Shen Yu; Yong-Shan Chen; Jia-Xi Peng (Environmental Science and Pollution Research, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

Assessing the real value of farmland in China - Rong Hu; Dao-chi Qiu; De-ti Xie; Xin-ya Wang; Lin Zhang (Journal of Mountain Science, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Clodronate-superparamagnetic iron oxide-containing liposomes attenuate renal injury in rats with severe acute pancreatitis - Sheng-chun Dang; Yan-hua Zeng; Ping-jiang Wang; Bao-ding Chen; Rong-fang Chen; Arun Kumar Singh; Pankaj Kumar; Shu Feng; Lei Cui; Hao Wang; Jian-xin Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

The rare intracellular RET mutation p.S891A in a Chinese Han family with familial medullary thyroid carcinoma - Xiao-Ping Qi; Rong-Xin Zhang; Jin-Lin Cao; Zhen-Guang Chen; Hang-Yang Jin; Ren-Rong Yang (Journal of Biosciences, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

Effect of Suaeda salsa on Soil Aggregate-Associated Organic Carbon and Nitrogen in Tidal Salt Marshes in the Liaohe Delta, China - Rong Mao; Xin-Hou Zhang; He-Nan Meng (Wetlands, 2014)

Perceptual quality assessment of SAR image compression - Anzhou Hu; Rong Zhang; Dong Yin; Yuan Chen; Xin Zhan (International Journal of Remote Sensing, 2013)

Isolation and characterization of fifteen polymorphic tetranucleotide microsatellite loci in Schizopygopsis younghusbandi Regan - Huan Zheng; Gui-Rong Zhang; Shan-Shan Guo; Kai-Jian Wei; Cong-Xin Xie; Tai-Ming Ge (Conservation Genetics Resources, 2013)

Functional transient receptor potential canonical type 1 channels in human atrial myocytes - Yan-Hui Zhang; Hui-Jun Wu; Hui Che; Hai-Ying Sun; Lik-Cheung Cheng; Xin Li; Wing-Kuk Au; Hung-Fat Tse; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

A Novel Peptide Can Mimic Extracellular Fibrinogen-Binding Protein to Block the Activation of Complement System - Ya-ping Gao; Jie Dong; Xin Zhang; Yu Liu; Qiang Lu; Jian-nan Feng; Xiao-rong Tan; Guang Yang (Cell Biochemistry and Biophysics, 2013)

Curcumin inhibits the metastasis of K1 papillary thyroid cancer cells via modulating E-cadherin and matrix metalloproteinase-9 expression - Chi-Yu Zhang; Li Zhang; Hui-Xin Yu; Jian-Dong Bao; Rong-Rong Lu (Biotechnology Letters, 2013)

Effect of sand-stabilizing shrubs on soil respiration in a temperate desert - Zhi-Shan Zhang; Xin-Rong Li; Robert S. Nowak; Pan Wu; Yan-Hong Gao; Yang Zhao; Lei Huang; Yi-Gang Hu; Rong-Liang Jia (Plant and Soil, 2013)

Bacterioplankton community structure in the Arctic waters as revealed by pyrosequencing of 16S rRNA genes - Yin-Xin Zeng; Fang Zhang; Jian-Feng He; Sang H. Lee; Zong-Yun Qiao; Yong Yu; Hui-Rong Li (Antonie van Leeuwenhoek, 2013)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Diversity of bacteria in surface ice of Austre Lovénbreen glacier, Svalbard - Yin-Xin Zeng; Ming Yan; Yong Yu; Hui-Rong Li; Jian-Feng He; Kun Sun; Fang Zhang (Archives of Microbiology, 2013)

Halomonas nanhaiensis sp. nov., a halophilic bacterium isolated from a sediment sample from the South China Sea - Mei-Rong Long; Dao-Feng Zhang; Xin-Yi Yang; Xiao-Mei Zhang; Yong-Guang Zhang; Yuan-Ming Zhang; Honghui Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Response of leaf, sheath and stem nutrient resorption to 7 years of N addition in freshwater wetland of Northeast China - Rong Mao; Chang-Chun Song; Xin-Hou Zhang; Xian-Wei Wang; Zheng-Hai Zhang (Plant and Soil, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Protective effect of whey protein hydrolysates against hydrogen peroxide-induced oxidative stress on PC12 cells - Qiu-Xiang Zhang; Yu-Fang Ling; Zhen Sun; Li Zhang; Hui-Xin Yu; Samuel Mburu Kamau; Rong-Rong Lu (Biotechnology Letters, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

The expression of a new HD-Zip II gene, MSHB1, involving the inhibitory effect of thidiazuron on somatic embryogenic competence in alfalfa (Medicago sativa L. cv. Jinnan) callus - Xin Hu; Chun-Rong Zhang; Hui Xie; Xia Huang; Yun-Feng Chen; Xue-Lin Huang (Acta Physiologiae Plantarum, 2012)

Associations between gene polymorphisms in fatty acid metabolism pathway and preterm delivery in a US urban black population - Xin Liu; Guoying Wang; Xiumei Hong; Hui-Ju Tsai; Rong Liu; Shanchun Zhang; Hongjian Wang; Colleen Pearson; Katherin Ortiz; Deli Wang; Emmet Hirsch; Barry Zuckerman; et al. (Human Genetics, 2012)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Differentiation and distribution of indica and japonica rice varieties along the altitude gradients in Yunnan Province of China as revealed by InDel molecular markers - Zhiyuan Xiong; Shujie Zhang; Yunyue Wang; Brian V. Ford-Lloyd; Min Tu; Xin Jin; Yue Wu; Huanxin Yan; Xiao Yang; Ping Liu; Bao-Rong Lu (Genetic Resources and Crop Evolution, 2010)

Pro-protein convertase-2/carboxypeptidase-E mediated neuropeptide processing of RGC-5 cell after in vitro ischemia - Song-Shan Tang; Juan-Hui Zhang; Huan-Xin Liu; Dong Zhou; Rong Qi (Neuroscience Bulletin, 2009)

RETRACTED ARTICLE: Pro-protein convertase-2/carboxypeptidase-E mediated neuropeptide processing of RGC-5 cell after in vitro ischemia - Song-Shan Tang; Juan-Hui Zhang; Huan-Xin Liu; Dong Zhou; Rong Qi (Neuroscience Bulletin, 2009)

Distribution, biomass, and dynamics of roots in a revegetated stand of Caragana korshinskii in the Tengger Desert, northwestern China - Zhi-Shan Zhang; Xin-Rong Li; Li-Chao Liu; Rong-Liang Jia; Jing-Guang Zhang; Tao Wang (Journal of Plant Research, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

Changes in Soil Microbial Community Associated with Invasion of the Exotic Weed, Mikania micrantha H.B.K - Wei-hua Li; Cong-bang Zhang; Hong-bo Jiang; Guo-rong Xin; Zhong-yi Yang (Plant and Soil, 2006)

Pharmacokinetics of three proton pump inhibitors in Chinese subjects in relation to the CYP2C19 genotype - Hai-Ling Qiao; Yu-Rong Hu; Xin Tian; Lin-Jing Jia; Na Gao; Li-Rong Zhang; Yu-Zhong Guo (European Journal of Clinical Pharmacology, 2006)

Thermal effects of building’s external surfaces in city - Yi-ping Zhang; Yun-ling He; Yu-hong Liu; You-xin Ma; You-rong Li; Jun-xia Dou (Chinese Geographical Science, 2004)

Developing gene-tagged molecular markers for functional analysis of starch-synthesizing genes in rice (Oryza sativa L.) - Xinyan Liu; Minghong Gu; Yuepeng Han; Qing Ji; Jufei Lu; Shiliang Gu; Rong Zhang; Xin Li; Jianmin Chen; Schuyler S. Korban; Mingliang Xu (Euphytica, 2004)